Hypopharyngeal schwannoma: A rarecase presentation and review ofliteratures - Ahmed, Abdulazeez; Umar, Ali; Aluko, Abdulakeem; Yaro, Mustapha (Nigerian Journal of Basic and Clinical Sciences, 2026)
Schwannomas are benign tumors of nerve cells and are particularly quite rare in the hypopharynx. To our knowledge only nine cases have been reported world-wide. We present a 27-year-old Hausa/Fulani housewife who developed slowly progressive and unremitting hoarseness and foreign body sensation in the throat. She had indirect laryngoscopy at presentation with subsequent examination under anesthesia, which revealed a soft ovoid pinkish swelling arising from the posterior pharyngeal wall in the hypopharynx. After a preliminary tracheotomy, the mass was mobilized and delivered trans-orally. She made an uneventful recovery and was discharged home. This uncommon presentation further emphasizes the dilemma of access and approach posed by hypopharyngeal masses.
Keywords: Hoarseness; hypopharynx; schwannoma; transoral